Optimization and testing of a mechanical roller seeder based on DEM-MBD rice potting tray - Jin, Xin; Chen, Zhuo; Zhao, Lijun; Zhao, Bo; Li, Mingyong; Zhou, Linyong; Ji, Jiangtao (Computers and electronics in agriculture, 2024)
•A double-slot seed filling port was designed for a rice mechanical roller seeding device.•A high-precision simulation model of three rice seeds was established.•DEM-MBD simulation was used to optimize the filling port of the rice potting tray mechanical roller seeding device.•Design-Expert was used to obtain the optimal solution of parameter combination for three seed filling ports. Seeder is the key component of rice seeding equipment, and its seed filling effect will directly affect the quality of seeding. This paper optimized the size parameters of the seed filling port based on DEM-MBD simulation technology. In this study, Y Liangyou 1998, Shen Liangyou 5814, and Yi Xiangyou 1108 were used as material subjects, analyzed the physical and mechanical characteristics, constructed the simulation model of rice seeds with a 3D laser scanner, and completed coupling simulation tests. The simulation results were analyzed using Design-Expert data analysis software to establish the optimization regression equation of the seed filling port and explore the optimal solution of the parameters of the seed filling port. The optimized filling port chamfer angle adapted to Y Liangyou 1998 was 45.84°, the fillet radius was 7.05 mm, the filling port length was 13.38 mm, and the predicted filling rate was 98.25 %. The optimized filling port chamfer angle adapted to Shen Liangyou 5814 was 46.10°, the fillet radius was 7.12 mm, the filling port length was 14.38 mm, and the predicted filling rate was 98.28 %. The optimized filling port chamfer angle adapted to Yi Xiangyou 1108 was 46.38°, the fillet radius was 7.06 mm, the filling port length was 15.41 mm, and the predicted filling rate was 98.52 %. Finally, specialized seeding trials and generalized seeding trials were showed that when seeding with the corresponding seeds of seeding rollers respectively, the seeding uniformity was kept above 66 %, the seeding qualification rate was kept above 96 %, and the seeding missed rate was below 1.3 %. When seeding with seeding rollers of maximum size seed-optimized, the seeding uniformity was kept above 65 %, the seeding qualification rate was kept above 95 %, and the seeding missed rate was below 1.3 %, where the maximum value of the seeding uniformity was 67.07 %, the minimum value of the seeding missed rate was 0.63 %, and the maximum value of the seeding qualification rate was 97.79 %. These results indicate that the rice potting tray mechanical roller seeder optimized based on DEM-MBD meets the requirements of precision seeding and can provide a reference for improving the seeding quality of high-speed rice seeding assembly lines.